2018
DOI: 10.3390/sports6030063
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Athletes during Training Camps: Observations and Translatable Strategies from Elite Road Cyclists and Swimmers

Abstract: Monitoring is an essential yet unstandardized component of managing athletic preparation. The purpose of this paper is to provide insight into the typical measurements and responses observed from monitoring elite road cyclist and swimmers during training camps, and translate these observations to practical strategies for other practitioners to employ. Twenty-nine male professional cyclists, 12 male and 19 female international swimmers participated in up to three of the eight 4–19 day training camps, held early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 27 publications
3
24
1
Order By: Relevance
“…40,44,45 Sleep loaded relatively equally on both principal components 1 and 2 which, given the importance of sleep to both physical and psychological recovery makes intuitive sense. 46 Acute physiological responses such as delayed onset of muscular soreness have been shown to contribute to poor sleep quality 3 while poor sleep quality is known to affect psychological factors such as “mood” or “stress”. 47…”
Section: Discussionmentioning
confidence: 99%
“…40,44,45 Sleep loaded relatively equally on both principal components 1 and 2 which, given the importance of sleep to both physical and psychological recovery makes intuitive sense. 46 Acute physiological responses such as delayed onset of muscular soreness have been shown to contribute to poor sleep quality 3 while poor sleep quality is known to affect psychological factors such as “mood” or “stress”. 47…”
Section: Discussionmentioning
confidence: 99%
“…Elite athletic preparation requires a fine balance between pushing the training and adaptation boundaries for performance, and avoiding negative outcomes, such as underperformance, injury, illness, or poor well-being [3,70]. Inappropriate loading may lead to excessive accumulated fatigue and maladaptive processes and increase injury risk by impairing factors, such as decision-making ability, coordination, and neuromuscular control.…”
Section: Training Periodizationmentioning
confidence: 99%
“…A multivariate approach, including physiological, biomechanical, cognitive, and perceptive monitoring, has been recommended to prevent maladaptation in highly trained triathletes [73]. Similarly, a recent study on the monitoring of professional road cyclists and elite swimmers during training camps provided further support for a multi-faceted approach to monitoring fatigue, recovery, and adaptation [70]. Furthermore, focusing on individual rather than group responses [72] and/or comparing individual to group day-to-day change in monitored variables may prove effective in flagging athletes potentially at risk of maladaptation [70].…”
Section: Training Periodizationmentioning
confidence: 99%
“…Therefore, training should be manipulated accordingly to bring about such improvements. Training and racing can be quantified through completed hours or distance, and using external (power output, total work) and internal (heart rate, rating of perceived exertion) training load measures [ 5 , 6 , 15 ]. Recent research demonstrated that training load can also be quantified using ratios of volume and intensity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%